Desarrollo de una propuesta para la fabricación de biomasa usada para el proceso de producción de un psicobiótico (2022)
The objective of this document is the development of a biomass manufacturing proposal for the psychobiotic production process, through the selection of the strain with the greatest psychobiotic potential through the investigation of different criteria of each preselected strain, in order to determine the ideal conditions for the growth of the microorganism and thereby propose a conceptual design of the production process. First, an exhaustive bibliographic review of those microorganisms previously studied in tests for their application in the field of psychobiotics was carried out, identifying Lactobacillus and Bifidobacterium species as the most investigated for this type of study. With this, a set of strains of these species were preselected, for which the ease of obtaining, culture medium, pH and temperature, level of development of the strain in the field of study and psychobiotic potential were evaluated. Based on the results obtained in the parameters studied, the strain with the highest score was selected.